Motor Vibration Analysis for the Fault Diagnosis in Nonstationary Operating Conditions - Hur, Jang-Wook; Tanvir Alam (International Journal of Integrated Engineering, 2020)
The reliability and performance of a system with minimum life-cycle cost have become quite prominent in engineering systems. With increasing industrial applications, machines are operating in intricate conditions with higher uncertainty, causing greater vulnerability of system failure. This paper reports fault-related information of Brushless DC Motor (BLDC motor) in nonstationary operating conditions and presents several analyses to diagnose the faults. Fault diagnosis is the most crucial and important part of system prognostics which helps to increase the remaining useful life (RUL) and prevent catastrophic failures. Having both electrical and mechanical characteristics present in a BLDC motor, it shows several faults in different operating conditions. These faults cause a significant change in the vibration of the Motor. This paper deals with the anomaly detection of BLDC motor in nonstationary speed conditions using vibration signal analysis as well as extraction of several Condition Indicators (CI).